Animal Experiment of a Novel Neurointerventional Surgical Robotic System with Master-Slave Mode - Keyun Liu; Yuhua Jiang; Youxiang Li (Applied Bionics and Biomechanics)
In order to inspect and improve the system performance of the neuro-interventional surgical robot and its effectiveness and safety in clinical applications, we conducted ten animal experiments using this robotic system. Cerebral angiography was performed on ten experimental animals, and various mechanical performance indicators, operating time, X-ray radiation dosage to the experimental animals and the experimenter, and arterial damage in the experimental animals were recorded when the robotic system completed cerebral angiography. The results show that the robotic system can successfully complete the cerebral angiography surgery, and the mechanical performance is up to standard. The operating time is almost the same as the physician’s operating time. And the mean X-ray radiation dosage received by the experimental animals and experimenter was 0.893 Gy and 0.0859 mSv, respectively. There were no complications associated with damage to the vascular endothelium. The robotic system can basically complete the relevant assessment indicators, and its system performance, effectiveness, and safety in clinical applications meet the standards, basically meeting the requirements of clinical applications of neurointerventional surgery.